CESifo World Economic Survey November 2012 - Johanna Plenk; Gernot Nerb; Klaus Wohlrabe; Michael Kleemann (CESifo World Economic Survey, 2012)
World economic climate: World economic climate remains overcast - Economic expectations: Economic expectations less positive - Inflation: Slightly increased price expectations - Currencies: Rise of US dollar expected to slow down - Interest Rates: Stable interest rates expected - Special Topic: Anti-Corruption Clause
Keywords: 330; World Economiy Survey; World Economic Climate; Economic Expectations; Inflation; Interest rates; Currencies